Curcuma mangga Val. Extract as Antidiabetic Agent in 3T3-L1 Adipocyte Cells - Dwiyati Pujimulyani; Wisnu Adi Yulianto; Astuti Setyawati; Rizal Rizal; Rismawati Laila Qodariah; Zakiyatul Khoiriyah; Annisa Arlisyah; Wahyu Widowati (Molecular and Cellular Biomedical Sciences, 2020)
Background: With the increase of diabetes mellitus (DM) prevalence, natural product emerged as complementary source on the development of new drug for this disease. White saffron (Curcuma mangga Val.) is a widely available plant found in Indonesia which often used traditionally as medicine for various ailment. Unfortunately scientific evidence of its antidiabetic activity has not been described very well. Present study was trying to evaluate the antidiabetic potential of white saffron based on the change of lipid accumulation.Materials and Methods: Cells viability assay was done using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) reagent to determine the safe concentrations of C. mangga Val. extract and its fractions including hexane, ethyl acetate, butanol, ethanol, water fractions and curcumol for the further assay. The preadipocyte cells (3T3-L1) were grown and differentiated into adipocyte cells using 3-isobutyl-1-methylxanthine (IBMX), dexamethasone and insulin. The adipocyte cells were treated with C. mangga Val. extract (CME) (the safest fraction at all concentrations) for 24 h. Oil red O staining was used to measure the lipid accumulation in adipocyte cells.Results: The CME was not toxic and able to decrease the lipid droplets of the 3T3-L1 adipocyte cells.Conclusion: The CME has potential antidiabetic activity due to ability to decrease the lipid droplet without disturbing the viability of the 3T3-L1 adipocyte cells.Keywords: white saffron, Curcuma mangga Val., antidiabetic